IMPROVING STUDENT LEARNING ACTIVITIES THROUGH REALISTIC MATHEMATICS APPROACH - Mega Ratrisna Dyah Ayu Pamungkas; Abdul Taram (Universitas Ahmad Dahlan, 2017)
This research was carried out because of the activities of the eighth-grade students of SMP Muhammadiyah 2 Prambanan in the 2015/1016 school year in mathematics learning was still lacking. The purpose of this study is to increase the activity of students in mathematics learning by using the Realistic Mathematics Approach class VIII Even Semester SMP Muhammadiyah 2 Prambanan 2015/2016 academic year. This research is a classroom action research. The settings used are class VIII, amounting to 27 students. The study was conducted in 2 cycles, namely, cycle I and cycle II, each cycle consisted of 2 meetings. Cycle I and cycle II used the Realistic Mathematics Approach. Data collection techniques used were observation, interviews, documentation, and triangulation. Research instruments are observation sheets and interview guidelines. Instrument analysis uses content validity. The analysis used is descriptive qualitative. The results showed that learning using the Realistic Mathematics Approach can improve student activity in mathematics learning in class VIII SMP Muhammadiyah 2 Prambanan 2015/2016 academic year. This is evident from the results of observations of student activities in learning each cycle has increased, namely the average percentage of observation of student activities in the first cycle of 50,623% which reached sufficient criteria, and in the second cycle increased to 61,960% which reached good criteria. The results of interviews with students showed a positive response to student learning activities.